Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acs.biomac.1c01636
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Exosomes Using Atom Transfer Radical Polymerization-Based Hydrogels

Abstract: Exosomes are 30−200 nm sized extracellular vesicles that are increasingly recognized as potential drug delivery vehicles. However, exogenous exosomes are rapidly cleared from the blood upon intravenous delivery, which limits their therapeutic potential. Here, we report bioactive exosome-tethered poly-(ethylene oxide)-based hydrogels for the localized delivery of therapeutic exosomes. Using cholesterol-modified DNA tethers, the lipid membrane of exosomes was functionalized with initiators to graft polymers in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Nucleic acid-polymer conjugates represent another important class of biohybrids used as multifunctional biomaterials in nanoscience and biomedicine. 91,104,[108][109][110] Therefore, we decided to use the EY/Cu technique to gra polymers from DNA. A 23mer DNA-based macroinitiator (DNA-iBBr) with a-bromoisobutyrate group at the 5 ′ -end was prepared in a DNA synthesizer 111 and then extended with OEOMA 500 , and molar ratios of [OEOMA 500 ]/[DNA-iBBr]/[EYH 2 ]/[CuBr 2 ]/[TPMA] ¼ 600/1/0.03/ 0.6/1.8 at a low reaction volume of 250 mL (Fig.…”
Section: Synthesis Of Biohybridsmentioning
confidence: 99%
“…Nucleic acid-polymer conjugates represent another important class of biohybrids used as multifunctional biomaterials in nanoscience and biomedicine. 91,104,[108][109][110] Therefore, we decided to use the EY/Cu technique to gra polymers from DNA. A 23mer DNA-based macroinitiator (DNA-iBBr) with a-bromoisobutyrate group at the 5 ′ -end was prepared in a DNA synthesizer 111 and then extended with OEOMA 500 , and molar ratios of [OEOMA 500 ]/[DNA-iBBr]/[EYH 2 ]/[CuBr 2 ]/[TPMA] ¼ 600/1/0.03/ 0.6/1.8 at a low reaction volume of 250 mL (Fig.…”
Section: Synthesis Of Biohybridsmentioning
confidence: 99%
“…As encapsulating exosomes within the hydrogel network can effectively prolong exosome release and consumption for enhancing therapeutic efficacy [ 39 , 40 ], OE-MSC-Exos were loaded into silk fibroin based photo-crosslinkable hydrogel (SFMA). Photographs in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Yerneni et al. [ 124 ] designed an ATRP-based hydrogel (using cholesterol-modified DNA tethers, the lipid membrane of exosomes was functionalized with initiators to graft polymers in the presence of additional initiators and crosslinker using photoinduced ATRP) for the controlled release of EVs and found that the release time of EVs was significantly prolonged up to one month. This hydrogel delivery system showed great potential.…”
Section: Hydrogelsmentioning
confidence: 99%
“… [ 23 ] Atom transfer radical polymerization (ATRP) nonactivated macrophages J774A.1 30–150 ​nm up to one month The monomer-to-crosslinker ratio (molar ratio) and the crosslinking density of the polymer networks both affect the release of EVs. [ 124 ] Ureido-pyrimidinone (UPy) supramolecular (PEG coupled to two UPy units) CPCs 100 ​nm up to 2.5 weeks The molecular weight of the PEG block within it may result in different kinetics of release. With a PEG block of 10 ​kg ​mol −1 (UPy10 ​k) showed a steadier release than UPy20 ​k.…”
Section: Underlying Mechanisms Affecting the Loading And Release Of Evsmentioning
confidence: 99%